A parametric study for optimization of minichannel based battery thermal management system. (25th May 2019) - An, Z.; Shah, K.; Jia, L.; Ma, Y.
Highlights: A simplified model for the optimization of battery thermal management system. Optimization of minichannel-based battery thermal management system. One half of the cell surface on single side of the cell is sufficient for cooling. Guidelines for design of minichannel-based BTMS for industrial application. Abstract: Minichannel technology has been shown to be a promising solution for the battery thermal management system (BTMS). Since the design space of the BTMS using minichannel technology consists a large number of parameters, performing parametric study and optimization of such a system is challenging. To overcome this challenge, a simplified numerical model is developed. In this model, effective convective heat transfer ( heff ) boundary condition is used at the cell-minichannel interface to circumvent simulating conjugate heat transfer and fluid flow in the minichannel. After validation with past work based on a three-dimensional conjugate heat transfer model, the simplified model is used to conduct a parametric study to determine the effect of various design and operation parameters on the performance of the BTMS. For the proposed BTMS, it is found that cooling half of the cell surface on single side of the cell is enough to keep the maximum temperature difference in the pack to be less than 3 °C at 2C discharge rate. At module level, it has been found that minichannel cooling on only one side of the cell or on every other cell can significantly increase the system level energy density. The results from the parametric study would be useful in designing a robust, effective, and economical minichannel-based BTMS for Electrical Vehicles.